A fast fracture approach to assess hydrogen embrittlement (HE) susceptibility and mechanism(s) of high strength martensitic steels. (September 2021) - Das, Tuhin; Brahimi, Salim V.; Song, Jun; Yue, Stephen
Graphical abstract: Highlights: A rapid fracture test is proposed to assess HE susceptibility and mechanism(s). Stress coupled H diffusion FEA model is developed to simulate the fast fracture test. Potential of the HE test is established in correlation to different sets of analysis. Fundamentals on the role of strength, microstructure and plasticity is demonstrated. A mechanistic description rooted in HEDE mechanism is presented. Abstract: A newly proposed rapid fracture test in four-point bending was used to test two different combinations of three quench and tempered steels, having: (a) similar strength levels with different steel chemistries, (b) different strength levels with same steel chemistry, with and without pre-charging of hydrogen. The test results show significant differences in HE susceptibility among the materials in both cases. The essential fractographic features pertinent to the HE failure of martensitic steels remain evident, despite fast loading. The study establishes the potential of the HE test in assessing susceptibility, further indicating significant influences of local plasticity and micromechanics on HE.